Information management and big data : second Annual International Symposium, SIMBig 2015, Cusco, Peru, September 2-4, 2015, and third Annual International Symposium, SIMBig 2016, Cusco, Peru, September 1-3, 2016, Revised selected papers /: second Annual International Symposium, SIMBig 2015, Cusco, Peru, September 2-4, 2015, and third Annual International Symposium, SIMBig 2016, Cusco, Peru, September 1-3, 2016, Revised selected papers. (2017) - Unknown
No abstract available